Cross-sectional evaluation of an internet-based hearing screening test in an occupational setting - Sheikh Rashid, Marya; Leensen, Monique CJ; de Laat, Jan APM; Dreschler, Wouter A. (Scandinavian Journal of Work, Environment & Health, 2017)
' ' OBJECTIVES ': 'The Occupational Earcheck (OEC) is an online internet test to detect high-frequency hearing loss for the purposes of occupational hearing screening. In this study, we evaluated the OEC in an occupational setting in order to assess test sensitivity, specificity, and validity. ' ' METHODS ': 'A cross-sectional study was conducted in 2015, in which the optimized OEC was evaluated on 94 employees from the army and three different companies in construction and manufacturing. Subjects underwent OEC in an office-like room. Pure-tone air conduction audiometry was performed as a reference test. The OEC was repeated for a subset of subjects (N=19). Important test characteristics (ie, sensitivity and specificity, test validity, and test–retest reliability) were assessed. ' ' RESULTS ': 'When analyzed on the individual level, the sensitivity and specificity of OEC were 90% and 77%, respectively. The speech reception threshold results correlated strongly with the pure-tone average of the frequencies 3, 4 and 6 kHz, reflecting good test validity (r=0.79). The difference between test and retest was not significant. The intra-class correlation coefficient was moderate (r=0.57), indicating a reasonable agreement between test and retest. ' ' CONCLUSIONS ': 'The OEC appears to be a suitable test for the detection of high-frequency hearing loss among noise-exposed employees, with good sensitivity and specificity values, even when performed in a semi-controlled occupational setting, though a possible learning effect should be taken into account.
Keywords: audiometry; cross-sectional evaluation; hearing; hearing screening test; internet-based; noise; noise-induced hearing loss; occupational high-frequency hearing loss; occupational noise; prevention; speech-in-noise; test sensitivity; test specificity